Emerging adult women's career role modeling and wishful identification with female TV news personalities. Issue 1 (1st January 2019) - Wenhold, Halie; Harrison, Kristen
Abstract : This study investigated how emerging adult women perceive, role model, and wishfully identify with female television news personalities (TVNPs) in the contemporary climate of social media celebrity where a male-dominated newsroom persists. Participants (n = 138, M = 19.58 years) selected TVNPs and completed survey measures of exposure, personal work values, perceived TVNP work values, and wishful identification. Participants' perceived extrinsic and intrinsic work values of TVNPs correlated with their own work values, extrinsically and intrinsically. Exposure to TVNPs predicted greater wishful identification. The discussion explores women's perceptions of TVNPs as they formulate career plans.